Arch bars in the mouth for 17 years - A case report - Vikas Sandilya; Neelam Noel Andrade; Paul C. Mathai; Natarajan Chelappa Balaji (Elsevier, 2018)
Arch bars are commonly used in maxillofacial surgery but their intraoral presence for an extremely long period is quite uncommon or rare. So when such a patient reports and denies having any complaints all these years, the question that presents is, how is this possible? What kept the patient so long? A review of the existing literature shows, despite being common in trauma care, failure to follow-up has not received the due attention. This study retrospectively reviews the various factors implicated for failure to follow-up and the proposed corrective measures. The objective is to identify such potential patients beforehand thereby facilitating efficient trauma care.